Identifying Active Compounds and Mechanism of Camellia nitidissima Chi on Anti-Colon Cancer by Network Pharmacology and Experimental Validation. (26th August 2021) - Chen, Yiwei; Hao, Erwei; Zhang, Fan; Du, Zhengcai; Xie, Jinling; Chen, Feng; Yu, Chunlin; Hou, Xiaotao; Deng, Jiagang
Abstract : Camellia nitidissima Chi (CNC) is a traditional Chinese medicine (TCM) with anticancer property. However, its underlying mechanisms of anti-colon cancer (CC) remain unknown. Therefore, a systematic approach is proposed in the present study to elucidate the anticancer mechanisms of CNC based on network pharmacology and experimental validation. Initially, the potential active ingredients of CNC were verified via the TCMSP database based on the oral bioavailability (OB) and drug-likeness (DL) terms. Hub targets of CNC were acquired from SwissTarget prediction and TCMSP databases, and target genes related to CC were gathered from GeneCards and OMIM databases. Cytoscape was used to establish the compound-target networks. Next, the hub target genes collected from the CNC and CC were parsed via GO and KEGG analysis. Results of GO and KEGG analysis reveal that quercetin and luteolin in CNC, VEGFA and AKT1 targets, and PI3K-Akt pathway were associated with the suppression of CC. Besides, the result of molecular docking unveils that VEGFA demonstrates the most powerful binding affinity among the binding outcomes. This finding was successfully validated using in vitro HCT116 cell model experiment. In conclusion, this study proved the usefulness of integrating network pharmacology with in vitro experiments in the elucidation of underlying molecular mechanisms of TCM.